2022
DOI: 10.1108/jpmh-03-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of autism spectrum screening questionnaire (ASSQ) for use in Georgian school settings

Abstract: Purpose Even though 95% of children with neurodevelopmental disorders, including autism spectrum disorder (ASD), live in low- and middle-income countries, there is a dearth of studies from these countries, including the Republic of Georgia. Several ASD screening tools are available, but few are validated for use in Georgian or other smaller countries. This study aims to adapt and validate the autism spectrum screening questionnaire (ASSQ) for use in Georgia. Design/methodology/approach The ASSQ was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Current screening assessments may not be sensitive enough to detect the clinical presentations of autistic females as ASD traits vary by age and sex, and the standardization studies still tend to be dominated by autistic male samples in many countries [13,27]. Additionally, autistic girls and women with ID, are disproportionately excluded from research, especially in studies that require self-report such as mental health [28].…”
Section: Sex Biases In Autism-related Symptoms Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Current screening assessments may not be sensitive enough to detect the clinical presentations of autistic females as ASD traits vary by age and sex, and the standardization studies still tend to be dominated by autistic male samples in many countries [13,27]. Additionally, autistic girls and women with ID, are disproportionately excluded from research, especially in studies that require self-report such as mental health [28].…”
Section: Sex Biases In Autism-related Symptoms Measuresmentioning
confidence: 99%
“…Additionally, autistic girls and women with ID, are disproportionately excluded from research, especially in studies that require self-report such as mental health [28]. For example, the Georgian adapted version of Autism Spectrum Screening Questionnaire (ASSQ) [29] lacked specificity in screening girls, with both parent-and teacher-report suggesting more work is needed to improve the screening ability of the Georgian version of ASSQs for use among girls [27]. Belcher et al [30] stress the importance of revising the Autism Spectrum Quotient (AQ) [31], as it emerged in their study that only two items out of 50 in AQ were gender unbiased.…”
Section: Sex Biases In Autism-related Symptoms Measuresmentioning
confidence: 99%
“…It was then validated, which successfully showed that the Indian version of ESCoT is appropriate for children aged 6–12. This could be very useful; the work is comparable to the Georgian adaptation of a related screening test: Zirakashvili et al (2022). (This paper has now attracted over 1,000 downloads.…”
mentioning
confidence: 99%